USE OF THERMAL IMAGING TECHNIQUES AND XANTHOPHYLLS CONTENT FOR DETERMINATION OF STRESS IN CORK OAK (QUERCUS SUBER L.) - Tronina, L; Grant, O M; Ramalho, J C; Chaves, M M (ACTA PHYSIOLOGIAE PLANTARUM, 2004)
Understanding the responses of cork oak (Quercus suber L.) to actual and predicted summer conditions is essential to determine the future sustainability of cork oak woodlands in Iberia. Thermal imaging may provide a rapid method for monitoring the extent of stress. The ecophysiology of cork trees was studied over three years. Three treatments were applied by means of rainfall capture and irrigation, with plots receiving 120%, 100%, or 80% of natural precipitation. Despite stomatal closure, detected using both thermal imaging and porometry, leaf water potential fell during the summer, most drastically during the third year of accumulative stress. The quantum efficiency (ΦPSII) and the maximum efficiency Formula of photosystem II also fell more intensely over the third summer, while non-photochemical quenching (NPQ) increased. The reduced precipitation treatment sporadically further reduced leaf water potential, stomatal conductance (gs), IG (an index of gs derived from thermal imaging), ΦPSII, and Formula, and increased leaf temperature and NPQ. It is concluded that these are very resilient trees since they were only severely affected in the third year of severe drought (the third year registering 45% less rainfall than average), and removing 20% of rainfall had a limited impact.
Key words: AS
Keywords: Quercus suber L.; Stress; thermal imaging